HATRA: THREE NOTES, HISTORICAL, ICONOGRAPHICAL, AND RELIGIOUS - al-Salihi, Wathiq (Iraq, 2021)
Historical NoteThe chronological table of rulers of Hatra includes an ambiguous person named Wrwd mrya, who supposedly succeeded Nshryhb mrya. Is he the latter's younger brother or older son? The epigraphical and sculptural evidence suggest that Nşru mrya, who followed Wrwd, is the son of Nshryhb mrya and was in fact Wrwd himself, who acquired the epithet or appellative Nşru, meaning the winner, protector, and defender. This epithet reflects that he led the Hatrenes and Arab tribes in their defence against the Roman army of Trajan in 116/117 A.D. Wrwd/Nsru commemorated his victory in a relief lintel in Shrine V at Hatra.Iconographical NoteThe excavators of Shrine I discovered the famous sculptured slab known as the Cerberus relief, depicting a god of the underworld with snakes and scorpions, thought to be an image of Nergal. However, the excavation of Shrine II revealed an altar, one side of which is carved in relief with a similar underworld deity with snakes. The other side of the altar is incised with an inscription mentioning a god Zqyqa. Thus, Zqyqa at Hatra is the god of the underworld, rather than Nergal.Religious NoteAn enigmatic statue was discovered in Shrine I, depicting a standing horned male. On the base is an Aramaic inscription mentioning the name Kenzw; he was identified as an ‘unknown god’. The excavation of Building A by an Italian team discovered a horned male statue with an inscription that referred to him as Hpyzw. It was originally placed on a podium set against the façade of the house courtyard. In front of the podium was an altar and evidence of ashes and burnt offerings. This context indicates that the horned statue of Hpyzw was worshipped and offerings were presented to him as a founder of the household. The similarity of the two statues suggests that a type of ancestor worship was practised at Hatra., التاريخية:عند كتابه تاريخ مدينة الحضر يواجه الباحث معضلة تتبع حكامها فقد بدات في عهد السادة اولهم نشر يهب مريا ثم يليه ورود مريا ولكن الاشارة اليه في النقوش تتوقف ثم يتبعه في الحكم و في النقوش نصرو مريا الذي ترك لنا انجازات معمارية عديدة وحقق النصر على جيوش الرومان بقياده تراجان وبصمود مدينة الحضر بقيادته نراه يحتفل بانتصاره في لوحه بالنحت البارز على مدخل المعبد الصغير الخامس وفي الحقيقة ان ورود مريا هو نفسه نصرو مريا وان كلمه نصرو صفه ونعت تعني المنتصر او المدافع او الحامي وقد استمرت في التداول بدلا عن اسم ورود.:الفنيةخلال تنقيبات المعبد الصغير الاول عثرالمنقبون على لوحه بالنحت البارز تصور اله العالم الاسفل مع الكلب ذو ثلاثه رؤوس سربيروس الذي كان يحمي باب العالم الاسفل في الاساطير الاغريقية وهو محاط بعقارب وثعابين وسميت تلك اللوحة باسم لوحة نرجول اله العالم الاسفل في الاساطير العراقية القديمة و عثر المنقبون في المعبد الصغير الثاني علي نصب لحرق البخور على واجهته يظهر شخص مشابه للوحة السابقة اشعث الشعر ويحمل ثعابين بيده وعلى واجهه النصب الجانبية نقش يذكر اسم الاله زقيقا وهذا يدل على ان الشخص المصورهو الاله زقيقا بصفته اله العالم الاسفل في معتقدات الحضريين وان نرجال في الحضر قد تطابق مع هرقل العاري الاله والبطل عند الاغريق.:الدينيةعثرعلى تمثال لشخص يدعى كنزي عند تنقيبات المعبد الصغير الاول وعلى جبهته قرنان صغيران والقرون تعني ان الشخص المصور اله فلذلك نعت هذا التمثال بالاله المجهول وعثرعلى تمثال في باحه البناية السكنية (A) و كان يوضع في الاصل على منصه وقريبا منها عثر علي مذبح وحوله اثار رماد و قرابين محروقة مما يشير الى ان التمثال كان يعبد ويقدم له القرابين وهذا التمثال يعود لشخص اسمه حفيزو وهو ايضا يحمل قرنين فوق جبهته . هذه الدلائل تشير الى ان كنزي وحفيزو عبدا كالهين وان عبادة الاسلاف قد امتدت الى مدينة الحضر و هذان التمثالان خير شاهد على ذلك .